How compatible are urban livestock and urban green spaces and trees? An assessment in a medium-sized South African town. Issue 3 (2nd September 2017) - Shackleton, C. M.; Guild, J.; Bromham, B.; Impey, S.; Jarrett, M.; Ngubane, S.; Steijl, K.
ABSTRACT: Urban green spaces and trees provide multiple benefits to urban residents and the sustainability of cities. A poorly examined benefit is the provision of fodder to urban livestock. However, the presence and activities of livestock may be incompatible with other uses, although this has been little studied. We examined the impacts of livestock on trees and parks along a gradient of declining livestock density, complemented with a tree planting experiment to monitor damage. Neighbouring residents and park managers were interviewed regarding their perceptions of damage caused by livestock. The negative impacts on soil compaction, tree damage and death increased with increasing livestock densities. Thorny tree species were damaged significantly less (13 %) than non-thorny species (77 %), as were protected trees (25 %) relative to unprotected ones (65 %). There was more tree damage in public green spaces (PUGS) (54 %) than control sites (38 %). The majority of local residents felt that livestock should not be allowed in formal PUGS, and most urban park managers regarded livestock damage as a strong disincentive to plant trees. These results show the need for management of the trade-offs caused by livestock and greater appreciation of livestock as agents shaping aspects of PUGS.